The Association of Multiple Identities with Self‐Directed Violence and Depression among Transgender Individuals. Issue 5 (24th February 2016) - Lytle, Megan C.; Blosnich, John R.; Kamen, Charles
Abstract : Transgender individuals have a high prevalence of self‐directed violence; however, there is scant literature focusing on their unique experiences. The differences in self‐harm, suicidal ideation, suicide attempt, and depression based on racial/ethnic identity and sexual orientation were examined among transgender individuals. Data were gathered from the Fall 2008 and Spring 2009 National College Health Assessment. Across racial/ethnic identities, greater proportions of transgender students endorsed self‐directed violence than their cisgender peers. Among transgender individuals, sexual minorities were more likely to report suicidal ideation than their heterosexual peers, and racial/ethnic minorities had higher odds of attempting suicide than non‐Hispanic White individuals.